Evolution of the diagnostic criteria of T-cell-mediated rejection of renal allografts: Banff classification updates II - Mubarak,Muhammed (2013)
The allo-specific immune responses to transplanted tissues or organs represent one of the most formidable challenges in the field of transplantation. Traditionally, cell-mediated alloimmune responses were considered the preeminent cause of rejection and have remained the focus of immunosuppressive drugs during the last several decades. More recently, attention has also been directed to the alloantibody-mediated damage and the innate immune system in initiating and effecting the immune injury to the transplanted organs. As a corollary to the above considerations, the earlier Banff classifications focused more on diagnosing and categorizing cellular rejection. There have occurred some significant changes in the cell-mediated rejection in recent Banff updates, but the changes are not as drastic or widespread, as those of the antibody-mediated rejection. Acute/active cell-mediated rejection may occur early or considerably late after renal transplantation. In this context, the terms of acute and chronic are not synonymous to their traditional connotations in pathology in terms of speed or duration of reaction. Acute rejection may occur many years after transplantation, and conversely, chronic changes may be present in the graft from the outset, derived from donor changes. Acute/active cell-mediated rejection, although markedly reduced in recent years, still remains one of the common causes of both acute and chronic renal allograft injury and dysfunction throughout the world. Luckily, a vast majority of cases of acute/active cell-mediated rejection respond rapidly and completely to the conventional anti-rejection treatment. In spite of this, it remains one of the most important causes of graft loss, especially in the long-term. Renal allograft biopsy still remains the gold standard test for an accurate diagnosis and categorization of cell-mediated rejection. A standardized approach to renal biopsy study is necessary if the full benefits of this invasive procedure are to be realized. Prior to the early 1990s, there were no uniformly accepted criteria for the diagnosis and classification of renal allograft pathology in general and rejection in particular. During early 1990s, a group of dedicated nephropathologists, clinicians and basic scientists set out to standardize the histopathological study of renal allograft biopsies for the uniform reporting of the pathological lesions across the world. These efforts have continued since then and have resulted in marked refinements in the diagnostic criteria and categories of rejection observed on renal allograft biopsies. The present paper forms the second attempt of the series to address the evolutionary changes in the diagnostic criteria and the classification of the rejection process on renal allograft biopsies as these took place over the years since the early 1990s. An earlier paper described in detail the changes that occurred in the category of antibody-mediated rejection. In this paper, we will discuss the changes that have occurred in the diagnosis and categorization of cell-mediated rejection and the focus, as in previous paper, will be on the morphological findings as observed on renal allograft biopsies.